Electrospinning of Polycaprolactone/Pluronic F127 dissolved in glacial acetic acid: fibrous scaffolds fabrication, characterization and in vitro evaluation. Issue 10 (3rd July 2018) - Li, Wenchao; Hu, Yiqiang; Shi, Lei; Zhang, Xianglin; Xiong, Liming; Zhang, Wancheng; Ullah, Ismat
Abstracts: The Polycaprolactone (PCL) fibrous scaffolds in nano to micro scale have been considered as excellent templates for cell culture and tissue growth. The hydrophobic nature of the PCL, however, yields low initial cell seeding density, heterogeneous cell spreading and slow cell growth rate. Therefore, in this study the surface hydrophilic fibrous scaffolds were directly fabricated by the electrospinning of PCL solutions with small quantities (0.5–5%) of Pluronic F127 (PEO100 -PPO65 -PEO100 ) dissolved in benign solvent of glacial acetic acid. The clear and miscible solutions were achieved by controlling the proper F127 content in the blend solutions. The continuous and smooth fibers with average diameters from 0.71 to 1.43 μm made up the fibrous scaffolds in non-woven mode. Then the water wetting angle of the scaffolds could be adjusted from 126° to 0° by varying F127 content owing to its hydrophilic PEO chains presented on surface the blended fibers. Finally, it was demonstrated that the blended fibrous scaffolds with the F127 content less than 1% exhibited better cell attachment, proliferation and spreading performance than those of pure PCL scaffolds.